Hospital admissions for HIV-infected prisoners in Italy. Issue 2 (12th June 2017) - Pontali, Emanuele; Ranieri, Roberto; Rastrelli, Elena; Iannece, Maria Donata; Ialungo, Anna Maria; Dell'Isola, Serena; Liberti, Alfonso; Rosario, Pietro; Casati, Rodolfo; Starnini, Giulio; Babudieri, Sergio
Abstract : Purpose: The purpose of this paper is to give a description of the clinical conditions and patient demographics of inpatient admissions of human immunodeficiency virus (HIV)-infected inmates in three hospital wards that provide hospital care for inmates in Italy. Design/methodology/approach: This is a retrospective review of hospital medical admissions of patients living with HIV from January 1 to December 31, 2014, in three Italian referral centers for hospitalization of inmates. Findings: A total of 85 admissions for 85 different HIV-infected inmates occurred in 2014 in the three centers participating to the study. Most patients (54.1 percent) were co-infected with hepatitis C. Discharge diagnosis largely varied ranging from common HIV-related co-morbidities to completely independent diagnosis. The most commonly observed discharge diagnoses were chronic hepatitis C, liver cirrhosis, opiate dependence and thrombocytopenia. Originality/value: Discharge diagnosis between HIV-infected inmates and HIV-infected patients in freedom are strikingly and significantly different. A large number of hospitalized HIV-infected inmates were affected by chronic viral hepatitis and liver cirrhosis; this is probably a direct consequence of the high prevalence of HCV and/or HBV co-infections in the inmate population in Italy. In addition, a significantly lower proportion of cancer diagnosis was observed among inmates; this is possibly justified by the fact that in our Italian settings when HIV infection is at advanced stages or if cancer treatment is started those affected are released from prison and can continue their diagnostic and treatment follow-up in freedom.